2018
DOI: 10.2337/db17-1449
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Sphingolipids, Insulin, HOMA-IR, and HOMA-B: The Strong Heart Family Study

Abstract: Experimental studies suggest ceramides may play a role in insulin resistance. However, the relationships of circulating ceramides and related sphingolipids with plasma insulin have been underexplored in humans. We measured 15 ceramide and sphingomyelin species in fasting baseline samples from the Strong Heart Family Study (SHFS), a prospective cohort of American Indians. We examined sphingolipid associations with both baseline and follow-up measures of plasma insulin, HOMA of insulin resistance (HOMA-IR), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
111
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(122 citation statements)
references
References 50 publications
(55 reference statements)
8
111
2
1
Order By: Relevance
“…Thus, most studies have focused on the more prevalent SMs and ceramides containing the double bond in the sphingoid base backbone. In fact, ceramides with C16:0, C18:0, C20:0, and C24:1 acyl chains are currently the subject of considerable interest because they have been linked to insulin resistance and risk of cardiovascular disease and mortality . While our association between dihydro‐SM and CRP is novel, the association with c‐peptide is consistent with findings for other sphingolipids and suggests that the dihydrosphingolipids may affect insulin secretion and metabolic health as well.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Thus, most studies have focused on the more prevalent SMs and ceramides containing the double bond in the sphingoid base backbone. In fact, ceramides with C16:0, C18:0, C20:0, and C24:1 acyl chains are currently the subject of considerable interest because they have been linked to insulin resistance and risk of cardiovascular disease and mortality . While our association between dihydro‐SM and CRP is novel, the association with c‐peptide is consistent with findings for other sphingolipids and suggests that the dihydrosphingolipids may affect insulin secretion and metabolic health as well.…”
Section: Discussionsupporting
confidence: 81%
“…One approach to identify those that do is to examine their relationship to parameters used to define metabolic health. The parameters that have been investigated to date include blood pressure , cholesterol, lipoprotein, and triglyceride levels , body composition , glucose, insulin and insulin sensitivity , adipokine levels , and inflammation markers . These studies have provided support for the involvement of some metabolites in processes related to metabolic diseases, such as the BCAAs in the development of insulin resistance , but the role of many of the metabolites associated with BMI remains undefined.…”
Section: Introductionmentioning
confidence: 99%
“…A recent large prospective study confirmed the significant and independent role of ceramides, in particular, the Cer(18:1/18:0)/Cer(18:1/16:0) ceramide ratio, in the prediction of Type 2 diabetes up to 10 years before the onset of the disease . Furthermore, specific ceramides are associated early with insulin resistance, prior to its progression to diabetes . This is intriguing given the fact that the early stages of diabetes are usually asymptomatic.…”
Section: Discussionmentioning
confidence: 88%
“…These data as well as the lipidomic data previously mentioned (Gonzalez‐Covarrubias et al, ; Montoliu et al, ; Wong et al, ) nicely justify further exploring the relationship between blood sphingolipids and human aging. Indeed, a recent study in nondiabetic patients found that higher levels of plasma insulin and an increased HOMA of insulin resistance score were associated with an elevation in plasma ceramides (Lemaitre et al, ).…”
Section: Lipid Biomarkers Of Aging In Humansmentioning
confidence: 99%